2021
DOI: 10.1002/adfm.202107941
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐Paper‐Based Electrodes on Plastic and Textile Supports as New Platforms for Amperometric Biosensing

Abstract: The possibility of exfoliating graphite into graphene sheets allows the researchers to produce a material, termed "graphene paper" (G-paper), conductive as graphite but more flexible and processable. G-paper is already used for electronic applications, like conductors, antennas, and heaters, outperforming metal conductors thanks to its high flexibility, lightness, chemical stability, and compatibility with polymeric substrates. Here, the effectiveness in the use of G-paper for the realization of electrodes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 80 publications
(97 reference statements)
0
8
0
Order By: Relevance
“…It retained above 97% of the response at 25 °C for NB, 4-NP, Pb 2+ , Cd 2+ , AA, and UA; this is attributed to the high physical and chemical stability of the carbon material, that is, GDY and graphene. 44,45 Furthermore, the UV−vis spectra of hemin/GDY/G were compared (Figure S12). It was found that the modified electrode had the same molecular structure before and after continuous detection, indicating that hemin loaded on the GDY/G heterostructure had excellent stability.…”
Section: Optimization Of Experimentalmentioning
confidence: 99%
“…It retained above 97% of the response at 25 °C for NB, 4-NP, Pb 2+ , Cd 2+ , AA, and UA; this is attributed to the high physical and chemical stability of the carbon material, that is, GDY and graphene. 44,45 Furthermore, the UV−vis spectra of hemin/GDY/G were compared (Figure S12). It was found that the modified electrode had the same molecular structure before and after continuous detection, indicating that hemin loaded on the GDY/G heterostructure had excellent stability.…”
Section: Optimization Of Experimentalmentioning
confidence: 99%
“…In conclusion, the manufactured IPEs behave as metal‐ or carbon‐based electrodes commonly used as sensor platforms so they can be therefore used as electrochemical platforms for analytical applications. [ 79 ]…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the manufactured IPEs behave as metal-or carbonbased electrodes commonly used as sensor platforms so they can be therefore used as electrochemical platforms for analytical applications. [79] We calculated the electrochemical area of the IPE from the CV measurements of Fc-COOH at different scan rates, applying the Randles-Sevcik equation. For IPEs, the electroactive area is 1.2 times larger than the geometrical one, while for commercial carbon screen printed electrodes (C-SPE) this ratio is close to 0.7.…”
Section: A Homogeneous Deposition Was Achieved Completely Covering Th...mentioning
confidence: 99%
“…Fabrics are developed to cover a variety of application needs, including flexible conductors, [ 20,21 ] sweat wicking, [ 22 ] water collecting, [ 23,24 ] and water transportation [ 25,26 ] due to their easy‐availability, hydrophilicity, porosity, and breathability. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fabrics are developed to cover a variety of application needs, including flexible conductors, [20,21] sweat wicking, [22] water collecting, [23,24] and water transportation [25,26] due to their easyavailability, hydrophilicity, porosity, and breathability. Zhang et al developed an atmosphere water harvesting fabric by using cellulose fabric's multiscale cellulose network and adsorptioncondensation mechanism.…”
Section: Introductionmentioning
confidence: 99%